Black tea extract prevents inorganic arsenic induced uncontrolled proliferation, epithelial to mesenchymal transition and induction of metastatic properties in HaCaT keratinocytes - an in vitro study. (December 2022) - Ghosh, Archismaan; Mukherjee, Sutapa; Roy, Madhumita
Abstract: A major global problem is chronic exposure to inorganic arsenic (iAs) which causes various health hazards including cancer. Escalation of reactive oxygen species (ROS) generation by chronic iAs exposure promotes Epithelial to Mesenchymal transition (EMT) which is followed by metastatic progression. In the present study, skin keratinocyte cells (HaCaT) were divided into three groups: (i) untreated, (ii) chronically iAs exposed, (iii) black tea extract (BTE) along with iAs treated. ROS was estimated by flowcytometry, expression of EMT markers were assessed by flowcytometry, western-blotting and Immunofluorescence. For metastatic studies, wound-healing assay, gelatin zymography, western-blot, transwell migration/invasion assay had been performed. Long term exposure of HaCaT cells to iAs causes excess generation of ROS. Morphological transformation and EMT were apparent at 210 days of exposure. Development of metastatic characteristics were observed at 240 days. Alterations in the parameters induced by iAs were found to be ameliorated by BTE. BTE was found to quench excess generation of ROS by iAs, subsequently inhibiting the chain of events like EMT and metastasis. Therefore, BTE may be considered as a potential phytochemical to prevent the deleterious effect of iAs. Skin carcinogenesis induced by iAs may thus be prevented by BTE via inhibition of EMT.